(untitled) (Historia, 2021)
In the article the author interrogates the lives of a range of early African political leaders in the first two decades of the twentieth century to argue that their attitudes to things British were more complex and ambiguous than hitherto perceived by historians. British liberalism and culture strongly influenced the early leaders of the ANC. After the denial of full South African citizenship to black people in 1910 and the imposition of harsh anti-African legislation, their leaders appealed to Britain and to a sense of 'British justice' based on their professed Empire loyalism. 'British' themes remained part of the plethora of identities of ANC leaders until at least the twenties but complicated the assertion of African identities. There were many ambiguities in African attitudes to the British World, which could range from support for 'the glorious British Empire' to more ironic or even derisory references to being 'slaves under the Union Jack'.